The Role of the Anterior Cingulate Cortex in Prediction Error and Signaling Surprise. (13th November 2017) - Alexander, William H.; Brown, Joshua W.
Abstract: In the past two decades, reinforcement learning (RL) has become a popular framework for understanding brain function. A key component of RL models, prediction error, has been associated with neural signals throughout the brain, including subcortical nuclei, primary sensory cortices, and prefrontal cortex. Depending on the location in which activity is observed, the functional interpretation of prediction error may change: Prediction errors may reflect a discrepancy in the anticipated and actual value of reward, a signal indicating the salience or novelty of a stimulus, and many other interpretations. Anterior cingulate cortex (ACC) has long been recognized as a region involved in processing behavioral error, and recent computational models of the region have expanded this interpretation to include a more general role for the region in predicting likely events, broadly construed, and signaling deviations between expected and observed events. Ongoing modeling work investigating the interaction between ACC and additional regions involved in cognitive control suggests an even broader role for cingulate in computing a hierarchically structured surprise signal critical for learning models of the environment. The result is a predictive coding model of the frontal lobes, suggesting that predictive coding may be a unifying computational principle across the neocortex. Abstract : This paper reviews the brain mechanisms responsible for surprise; focusing on the Anterior Cingulate Cortex (ACC), long‐known to play a role in behavioral‐error, with a recently‐expanded role in predicting 'likely' events and signaling deviations between expected and observed events. It argues for ACC's role in in surprise and learning, based on recent modelling work. As such, the paper provides the neuroscience complement to the psychological and computational proposals of other papers in the volume.